The Terrible Triad of Checkpoint Inhibition: A Case Report of Myasthenia Gravis, Myocarditis, and Myositis Induced by Cemiplimab in a Patient with Metastatic Cutaneous Squamous Cell Carcinoma. (4th July 2020) - Jeyakumar, Nikeshan; Etchegaray, Mikel; Henry, Jason; Lelenwa, Laura; Zhao, Bihong; Segura, Ana; Buja, L. Maximilian
Abstract : Background . We report a case of a patient with squamous cell carcinoma (SCC) who developed myasthenia gravis (MG), myositis, and myocarditis after receiving cemiplimab, an anti-PD-1 immune checkpoint inhibitor (ICI). Case Presentation. An 86-year-old man with metastatic periocular SCC presented with decreased vision in the left eye, severe fatigue, and lower back and bilateral hip pain 3 weeks after receiving cemiplimab. Within hours, he developed dysphonia, pharyngeal secretions, and dysphagia, necessitating intubation. Endomyocardial biopsy revealed active lymphocyte-mediated necrosis consistent with ICI-induced myocarditis. Anti-striated muscle and anti-acetylcholine receptor antibodies were elevated, consistent with myositis and myasthenia gravis. Despite plasma exchange therapy, steroids, and intravenous immunoglobulin, he died from cardiac arrest. Conclusions . The presence of myasthenia gravis, myocarditis, or myositis should prompt evaluation for all three toxicities as they may represent an overlap syndrome. The severity of these immunotoxicities highlights the need for clinicians to suspect multiple simultaneous adverse effects of ICIs.